Introvert dan Ekstrovert: TAPPS Model Terhadap Higher Order Thinking Skills (HOTS) Siswa Pada Pembelajaran Matematika - Nizami, Ahmad Wafa (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2022)
This study aimed to find out (1) the effect of TAPPS learning model on HOTS viewed from introverted and extroverted personality types of students, (2) the effect of learning without using the TAPPS model on HOTS viewed from introverted and extroverted personality types, and (3) the interaction between the learning model with and without TAPPS and the introverted and extroverted personality types to HOTS of the eighth-grade students of MTsN 1 Selat Kuala Kapuas. This study was quasi-experimental using a 2 x 2 factorial design. The independent variable of this study is the TAPPS model. The attributive variables are introverted and extroverted personality types and higher-order thinking skills. This study took a sample of 40 students from two classes consisting of 41 introverted students and 39 extroverted students. The instrument used was a higher-order thinking skills (HOTS) test and a personality-type questionnaire. The reliability coefficient of HOTS instruments for the pre-test was 0.784, and that for the post-test was 0.733 with SEMs of 0.527 and 0.586 respectively. The data were collected using one sample t-test and an independent t-test with a significance level of 0.05. The results of this study indicated that (1) there is an effect of the use of the TAPPS learning model on HOTS viewed from introverted and extroverted personality types of the eighth-grade students of MTsN 1 Selat in Kapuas Regency with an average score of above minimum mastery criteria and the significance the gain score of (p) 0,000 0.05; (2) there is a learning effect without using the TAPPS learning model on HOTS viewed from introverted and extroverted personality types of the eighth-grade students of MTsN 1 Selat in Kapuas Regency with an average score of above the minimum mastery criteria and the significance for the gain score of (p) 0,000 0.05; and (3) there is no interaction between the learning model and the personality types of students, both introverted and extroverted personality types, which means that the learning model with personality types does not affect HOTS